Potensi Sampah Organik TPS 3R Menjadi Biogas dan Pupuk (Studi Kasus: TPS 3R Kasih, Kabupaten Bantul, Daerah Istimewa Yogyakarta) - Titi Tiara Anasstasia; Oktavia Dewi Alfiani; Ayu Utami; Layla Azzahra Ari (G-Tech: Jurnal Teknologi Terapan, 2024)
The generation of organic waste at TPS 3R Kasih increased and dominated but its separation has not been carried out optimally. The purpose of this study was to determine the chemical characteristics of organic waste and analyze the potential for biogas that can be produced from organic waste anaerobically. The research method included sample collection using the purposive sampling method, surveys, and laboratory experiments using a batch or closed anaerobic reactor without any reactant movement to determine the potential for methane formation during 40 days of processing. The chemical characteristics of the slurry before and after processing were analyzed to determine its potential use after biogas formation as compost. The results showed that the slurry content before and after processing did not meet the fertilizer quality standards. Methane gas was formed starting on the 35th day in both reactors 1 and 2 with the highest concentration achieved at 1.2% of a mixture of organic waste, water, animal waste and EM4 with an optimum time of 40 days.